Performance Index-Based Multi-Criteria Optimization of GGBFS Replacement in Concrete for Enhanced Strength, Durability, and Sustainability - Mlodi, Lodgar Gabriel; Herry Suryadi Djayaprabha (Jurnal Teknik Sipil dan Perencanaan, 2025)
Using ground granulated blast furnace slag (GGBFS) as a partial replacement for ordinary Portland cement (OPC) has emerged as a sustainable alternative in concrete production, offering notable improvements in durability and long-term strength. However, identifying the optimal replacement level that balances mechanical performance, durability, and sustainability remains challenging. This study addresses this gap by critically reviewing sixteen peer-reviewed studies conducted between 2006 and 2025, the broadest dataset yet applied in a performance index (PI)-based evaluation. A PI was developed to normalize and compare diverse mechanical and durability parameters, integrating them into a multi-criteria framework. The PI was further evaluated under three practical weightings: Balanced (50/50), Durability-prioritized (60/40), and Strength-prioritized (40/60). Results indicate that a 40% GGBFS replacement delivers the highest composite performance under balanced criteria, 20% is optimal for strength-driven applications, and 60–70% provides superior durability in aggressive environments, especially when activation or enhanced curing is applied. This study demonstrates the practical utility of an integrated PI approach for sustainable concrete design.